Problematika Implementasi Pembelajaran Tematik Terpadu Pada Mata Pelajaran Matematika Dalam Kurikulum 2013 Di SD Muhammadiyah 24 Gajahan Surakarta - Warda, Marina Kusuma, Dra. Sri Hartini, S.H., M.Pd (2017)
This study aimed to describe problems and solutions implementation of integrated thematic learning in mathematics in the curriculum in 2013 at 24 Gajahan SD Muhammadiyah Surakarta. This type of research is qualitative research with case study research design. Data collection techniques used were interviews, observation and documentation. Examination of the validity of the data using triangulation techniques and resources. The process of data analysis: data reduction, data presentation and conclusion. The results of recent research shows that the problems faced by teachers are 1) the difficulty in understanding and interpreting the sentence of the basic competencies, 2) submission of Mathematics in thematic learning integrated just conveyed the basic concept only, 3) teachers do not have much time to do the deepening material, 4) delivery of materials for Mathematics is more dominant than the other subjects. Minimize solution to the problems above, namely 1) teachers had discussions with colleagues who are more familiar with integrated thematic learning, 2) teachers to communicate with parents, 3) the teacher provides additional hours outside the integrated thematic learning, 4) the headmaster facilited the teacher to follow training of kurikulum 2013. Keywords: Problems, Integrated Thematic, Mathematics